Lower extremity reconstruction: utility of smartphone thermal imaging camera in planning perforator based pedicled flaps - Afzal, Muhammad Omar; ul Haq, Ata; Riaz, Muhammad Ahsan; Nazeer Tarar, Moazzam; Fazeel Alvi, Hamid (Journal of Ayub Medical College Abbottabad, 2021)
Background: Presence of good size perforators are mandatory to design perforator based pedicelled flaps specially in lower limb as flap failure rate is relatively high. We have explored the use of smartphone based dynamic thermal imaging and compared it with doppler to devise a protocol for planning and execution of pedicled perforator flaps and described its use in deciding delay of flap. We have also compared the time required for detecting dominant perforators. Methods: This prospective case series was done at Jinnah burn and reconstructive surgery center Lahore from July to September 2018 and included patients requiring pedicled fasciocutaneous or musculocutaneous flap for lower extremity reconstruction. Smartphone based dynamic thermal imaging and doppler were used to map out suitable perforators and confirmed intraoperatively. Comparison was made regarding their ability to locate dominant perforators and total time required. Utility of thermal imaging to ascertain flap perfusion postoperatively was also assessed. Flaps were designed according to thermal mapping. Clinical judgement supplemented with thermal imaging was used to ascertain flap survival. Results: The study included 15 patients in which 22 out 23 dominant perforators as located with thermal imaging were confirmed intra-operatively (positive predictive value = 95.7%) as compared to 22 out of 32 with doppler (positive predictive value=68.8%). Mean time required with doppler was 591.27±252.48, compared to 598.47±192.94 seconds with thermal imaging. In two cases flap was delayed. Partial flap necrosis occurred in one case. Conclusion: Dynamic thermal imaging can be reliably used in planning of pedicled perforator flaps for lower limb reconstruction. We have found it more reliable than handheld doppler in locating dominant perforators. ps, Lower Extremity Reconstruction.